ZAKAT SEBAGAI ALTERNATIF PENDAPATAN NEGARA - Aditya Agung Satrio (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2022)
Zakat and tax have some similarities in function and role. Researches related to zakat only focus on the management and calculation method. There are still limited studies that discuss the possibility of Zakat being used as an alternative to state revenue. Therefore, this study aims to fill this gap by making a study of the possibility of zakat being used as a source of state revenue. This study uses a qualitative approach by reviewing various kinds of literature related to zakat management in various countries. The pieces of literature are processed using the procedure developed by Taylor (2017). The procedures are (1) organize; (2) synthesize, and (3) identify. Through this study, the results show that it is legally possible to include zakat as an alternative to receiving and can be used for social programs. the use of funds from zakat can be classified as restricted funds which can only be used for programs that comply with Islamic regulations. This research can be used as input to the Government to include zakat as state budget revenues. Â Keywords: Zakat; State Revenue; Syaria.